Influence of the Antarctic Oscillation on the South Atlantic Convergence Zone - Flávia Venturini Rosso; Nathalie Tissot Boiaski; Simone Erotildes Teleginski Ferraz; Tiago Capello Robles (Atmosphere, 2018)
The South Atlantic convergence zone (SACZ) is the main summer-typical atmospheric phenomenon occurring in South America, and it is of great interest because it regulates the rainy season in the most populated regions of Brazil. Frequency variability, persistence, and geographical position of the SACZ and its relationship with intraseasonal variability is well described in the literature. However, the influence of extratropical forcing on the SACZ is not well understood. Consequently, the aim of this study is to evaluate the role of the Antarctic Oscillation (AAO) in SACZ events. The persistence and frequencies of SACZ events, mean, standard deviation of total precipitation per event, lag composite of daily precipitation and geopotential height anomalies were obtained for each phase of the AAO. Therefore, frequency, persistence and total precipitation of SACZ events were higher in positive AAO (AAO+) than negative AAO (AAO−). A teleconnection mechanism between the extratropics and the SACZ region is evident in AAO+, through intensification of the polar and subtropical jets, in the days preceding SACZ. The same was not observed in the AAO−, where the anomalies were confined in the subtropical region and displaced to the South Atlantic Ocean.